Induction of maturation gonads the Asian swamp eel Monopterus albus at different sizes with the hormones PMSG + antidopamine and hCG - Aan Aryanti Sandra; Agus Oman Sudrajat; Harton Arfah; Dinar Tri Soelistyowati (Jurnal Akuakultur Indonesia)
Monopterus albus is a protogynous hermaphrodite species that undergoes a unidirectional sex change from female to male. Asian swamp eel cultivation activities face constraints in seeding due to limited mature gonad broodstock. This study aims to evaluate the effect of administering a combination of PMSG + Antidopamine (OodevⓇ) and hCG on the induction of gonad maturation of Asian swamp eels at various body sizes. The research design used was a factorial design consisting of control treatment (without hormone injection), P1 = hCG (dose 20 IU/kg), P2 = OodevⓇ (dose 0.5 ml/kg), and P3 = hCG+OodevⓇ (dose 20 IU+0.5 ml/kg) with body length groups, namely K1 (15–25 cm), K2 (30–40 cm), and K3 (45–55 cm). The results showed that eels in group K1 had the highest body length growth (3.63 ± 0.96 cm), while the highest body weight gain (5.30 ± 1.30 grams) in K3 (P<0.05). Administration of oodevⓇ showed the highest values ​​for GSI = 8.13 ± 0.72% and HSI = 4.36±0.80% in K1 compared to K2 (GSI = 6.95 ± 2.86%; HSI = 3.26 ± 0.68%) with female sex. In contrast, group K3 experienced a decrease in GSI = 0.81 ± 0.11% and HSI = 2.48 ± 1.06% accompanied by masculinization. Administration of oodevⓇ also increased the concentration of estradiol-17β in K1 and K2, while testosterone increased in K3. The conclusion of this study is that administering oodevⓇ to 15-40 cm sized Asian swamp eels can accelerate gonad maturity with female sex status, while at sizes >45 cm it can accelerate masculinization and maturation of male gonads.